2021
DOI: 10.33552/gjor.2021.03.000568
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ultrasound-Guided Techniques for Carpal Tunnel Release: A Descriptive Review

Abstract: Carpal tunnel syndrome (CTS) is a prevalent compressive peripheral neuropathy that often requires surgical treatment due to symptom severity or medical treatment failure. The recent popularity of ultrasound-guided (US) percutaneous surgery to treat these neuropathies has made this minimally invasive technique a good option over traditional open techniques. This review sought to identify, classify, and describe the minimally invasive percutaneous US-guided techniques reported in the literature for carpal tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several different techniques have been described. 68 A single-use disposable device has recently become available that uses expandable protective balloons to allow for a consistent carpal tunnel transverse safe zone while a retractable microknife cuts the TCL. 69 Leiby et al 70 reported on the 1-year follow-up for patients who underwent ultrasound-guided CTR and found statistically and clinically significant improvements in Boston Carpal Tunnel Questionnaire symptom severity and functional status scores as well as Quick Disabilities of the Arm, Shoulder, and Hand scores, with high patient satisfaction and no documented complications or recurrent symptoms.…”
Section: Treatment Of Compressive Neuropathiesmentioning
confidence: 99%
“…Several different techniques have been described. 68 A single-use disposable device has recently become available that uses expandable protective balloons to allow for a consistent carpal tunnel transverse safe zone while a retractable microknife cuts the TCL. 69 Leiby et al 70 reported on the 1-year follow-up for patients who underwent ultrasound-guided CTR and found statistically and clinically significant improvements in Boston Carpal Tunnel Questionnaire symptom severity and functional status scores as well as Quick Disabilities of the Arm, Shoulder, and Hand scores, with high patient satisfaction and no documented complications or recurrent symptoms.…”
Section: Treatment Of Compressive Neuropathiesmentioning
confidence: 99%